To Investigate the Phenomenon of Surface Modification in Die Steels Using EDM Process - Kumar, Sanjeev (My University, 2008)
Electrical Discharge Machining (EDM) has established itself as one of the most versatile machining process in the manufacture of press tools, dies and punches. In this process, a tool (electrode) cuts the work material by a series of electrical sparks generated in a dielectric medium and produces a mirror image of itself by advancing into the workpiece. Some of the reasons for the tremendous popularity of this process are its ability to machine complex internal shapes in hardened materials, negligible cutting forces because of absence of any physical contact between the tool and work material, distortion-free accurate machining, easy fabrication of the tool and simple operation of the machine. Though EDM is essentially a material removal process, a number of phenomena observed during machining make it a suitable technology for application in the field of surface improvement. Each spark generates a temperature in the range of 8,000 to 12,000 0C and creates a plasma channel; causing fusion or partial vapourization of the workpiece material, tool electrode and the dielectric fluid at the point of discharge. As the plasma channel collapses towards the end of the machining cycle, some of these constituents may get deposited on the machined surface under appropriate process conditions. Suitable alloying elements may be introduced in the tool electrode bodies or added to the dielectric medium in the form of fine powders for specific surface modifications. These elements may migrate to the machined surface either in free form or as carbides by combining with carbon generated from the breakdown of the hydrocarbon dielectric. The changes in chemical composition of the surface and its quenching by the flowing dielectric bring about desirable improvements in properties. Additive powders in the dielectric medium also change the sparking pattern and hence, significantly affect the properties of the machined surface. This research work has investigated the effect of EDM process on surface properties under machining conditions favouring material transfer to the workpiece surface from electrode bodies as well as from powders suspended in the dielectric medium. The experimentation was conducted on three of the most widely used die steel materials; namely Oil-Hardening Non-Shrinkable (OHNS type O2) die steel, High- Carbon High-Chromium (type D2) die steel and Hot work (type H13) die Steel. These materials were machined in two stages – first with four different electrode materials, and then with four different powders mixed in the dielectric medium. The four electrode materials were copper, graphite, copper-tungsten and inconel (an alloy of nickel, chromium and iron as main constituents). The four powders used for experimentation were graphite, manganese, silicon and tungsten. The study of existing literature in this area reveals that no work has been done on OHNS die steel which is a very important tool material for cold working applications. Inconel alloy has only been used as work material in EDM. If it is used as an electrode material, this alloy may contribute chromium and nickel to the plasma channel and consequently, to the workpiece surface. Likewise, no research work is available on the use of manganese powder in the dielectric. The effect of powder-mixed dielectric on output parameters such as material removal rate, tool wear rate and surface finish has been studied extensively but very few researchers have used this method for surface modification. Amongst the input process parameters, the effect of pulse off-time has been investigated as part of duty cycle and not as an independent variable. The most significant machining parameters and their ranges for this work were selected on the basis of pilot experimentation. Machining was carried out by using L9 orthogonal array of Taguchi experimental design. The input process parameters that constituted the orthogonal array were Peak current, Pulse on-time and Pulse off-time. Work material was not included as one of the factors in orthogonal array because the pattern of response of each work material to surface modification was expected to be different. The set of nine experiments were repeated for each combination of electrode material and work material during the first stage; and then for each combination of powder and work material during the second stage of experimentation. As the objective of the work was to study surface modification of die steels, no attempt was made to measure conventional output parameters such as material removal rate and tool wear rate etc. Micro-hardness and surface roughness measurements were carried out on all the machined samples and the data was analyzed as per Taguchi method to find out the best values of input process parameters for each combination of work material, electrode material and powder. Analysis of Variance (ANOVA) of the data revealed the significance and percentage contribution of the three factors. Confirmation experiments were conducted where the desirable machining parameters did not constitute one of the rows of the orthogonal array. Optimum values and relative contribution of the three input process parameters for each electrode material or the type of powder suspended in the dielectric medium were found to be almost same irrespective of the work material. On the other hand, the best values of micro-hardness and surface roughness achieved, depended on the work material. Peak current emerged as the most significant factor in all the experiments (more than 50 % contribution in all cases), followed by pulse on-time and then pulse off-time. However, in two cases, when machining was carried out with inconel electrode and with tungsten powder suspended in the dielectric medium, the contribution of pulse off-time was found to be more than pulse on-time. The improvement in micro-hardness in both these cases turned out to be very high. Good improvement in micro-hardness was also noticed when machining was carried out with copper-tungsten electrode and with manganese powder. Amongst the four electrode materials, copper-tungsten resulted in the best combination of micro-hardness and surface roughness. Machining with inconel electrode resulted in the transfer of nickel and chromium to the workpiece surface and an improvement in micro-hardness by as much as 88%. However, it was accompanied by a substantial deterioration of surface finish. Very good surface finish (of the order of 1 µm) was obtained when machining was carried out with graphite powder and also with silicon powder. Both the powders substantially improved Ra and Rz values of surface roughness, produced a crack-free surface and had some positive effect on micro-hardness. The measurements on surfaces obtained after machining with copper electrode (without any powder) served as reference values. However, the performance of graphite powder on both the counts was found to be better than silicon powder. Machining with graphite powder also resulted in free graphite on the workpiece surface which can be expected to provide self-lubricating property to it. The samples showing high values of micro-hardness or very good surface finish were further subjected to X-ray Diffraction analysis and then chemical composition analysis on Optical Emission Spectrometer to find out the phases and constituents of the surfaces. The microstructures were studied under a Scanning Electron Microscope. The results showed significant material transfer from the electrode bodies as well as from the powders suspended in the dielectric medium. In general, it was observed that less current and more pulse on-time were required for material transfer from suspended powders as compared to material transfer from electrode bodies. An increase in the percentage of carbon in the work materials was observed under all machining conditions and it was found that this carbon came from the pyrolysis of the hydrocarbon dielectric. An examination of the migration of carbon and tungsten by the two methods of surface modification was also done. Tungsten was found in the workpiece surfaces in the form of intermetallic compounds with iron (Fe2W, Fe7W6); as carbides (WC, W2C); or in the form of alloyed cementite [(FeW)3C]. All the three work materials showed more than 100 % improvement in micro-hardness when machining was carried out with tungsten powder mixed in the dielectric medium. Different forms of manganese carbide (Mn4C1.06, Mn7C3 and Mn5C2) were observed in the workpiece surface when manganese powder was added to the dielectric medium. Inconel alloy electrode contributed chromium and nickel to the workpiece surface in the form of an intermetallic compound (FeCrNi) and a solid solution (Fe-Ni). Some traces of silicon in elemental form and as a solid solution with iron (Fe-Si) were seen but formation of silicon carbide did not take place by this method. It can be concluded from this research work that surface modification of die steels by electrical discharge machining is technically feasible and simple modifications in the existing set-ups can lead to substantial improvement in surface properties. Higher surface hardness and better abrasion resistance will enhance the working life of dies and press tools.
Ph.D., MED
Keywords: EDM; Powder Mixed Dielectric; Surface Modification